Motivational Performance and Organizational Commitment among Healthcare Workers at a Health Center, Zarumilla, 2023 - Llatance Ruiz, Ingrid Del Pilar (2025)
Organizational behavior is a fundamental element in healthcare institutions, particularly in shaping organizational commitment, which determines the loyalty of healthcare personnel through motivational performance mechanisms. The present study aimed to determine the relationship between motivational performance and organizational commitment among healthcare workers at a healthcare center in Zarumilla during 2023. A quantitative, applied, descriptive-correlational design was implemented, working with a census population of 120 employees. Data collection was conducted through two structured questionnaires administered through digital Google forms, designed to measure both variables and establish their statistical correlation. The results showed that 14 employees (11.7%) presented low overall organizational commitment, of which 7 (50%) also reported low motivational performance, suggesting a direct association between both variables in this segment. A total of 74 employees (61.7%) registered a medium level of organizational commitment; Of these, 38 (51.4%) exhibited a medium level of motivation, while 19 (25.7%) achieved a high level of motivation, indicating that moderate commitment tends to be associated with medium or high motivation. Finally, 32 employees (26.7%) demonstrated high overall organizational commitment, ranging from high motivation (n=12, 37.5%) to medium motivation (n=19, 59.4%), with no cases of low motivation recorded in this group. It is concluded that there is a statistically significant relationship between motivational performance and organizational commitment among healthcare workers at the evaluated health center. The findings suggest that optimizing situational and relational factors could significantly increase levels of job satisfaction and organizational adherence among healthcare personnel. Keywords: Motivational performance, organizational commitment, healthcare workers.